(untitled) (Bangladesh Critical Care Journal, 2021)
Background: Most of the currently used scoring systems can effectively predict mortality in critically ill patients, however, most of these scores are time-consuming to calculate and require laboratory parameters that are not readily available, limiting feasibility in low- and middle-income countries (LMICs). Objectives: To compare modified Sequential Organ Failure Assessment (mSOFA) and Sequential Organ Failure Assessment (SOFA) scores to predict mortality among the critically ill patients. Design: Prospective, observational, single centre cohort study. Method: Patients surviving more than 48 hours in the Intensive Care Unit (ICU) of Tribhuvan University Teaching Hospital, Kathmandu, Nepal were enrolled in the study. Data were collected prospectively. SOFA and mSOFA scores were calculated at the time of admission and after 48 hours of stay in ICU. Patients were followed up until ICU discharge to document their survival status. Area under the receiver operating characteristic (ROC) curve was used to compare the two scores. Results: Our study enrolled 100 critically ill patients during the study period with the mean age of 46 years (SD=17) and 43% male patients. Out of 100 patients, 37 died during the study period. The day 1, day 3, mean, delta, maximum, and total SOFA score were higher in non-survivors than in survivors. Similarly, the day 1, day 3, mean, delta, maximum and total mSOFA score was higher in non-survivors compared to the survivors. We found that the day 1 SOFA score predicted mortality better than the day 1 mSOFA score with an area under curve (AUC) of 0.79 (95% CI, 0.70-0.88) and 0.73 (95% CI, 0.64-0.83) respectively. While, day 3 SOFA and mSOFA scores performed equally well in predicting the mortality with AUC of 0.91 (95% CI, 0.85-0.96) and 0.92 (95% CI, 0.88-0.97) respectively. Conclusions: Performance of mSOFA score was comparable to SOFA score for prediction of ICU mortality, when calculated at day 3 of admission. The mSOFA score can be an effective and feasible tool to predict outcome in places with resource limitations and during pandemics. Bangladesh Crit Care J September 2021; 9 (2): 74-78